LOSER Climate Engineering Algae Bloom Climate-change Scheme Doomed. - Upson, S.
Foster City-based Planktos's main goal is to spread iron dust over great swaths of the ocean, where it will feed vast blooms of surface phytoplankton that will suck carbon dioxide out of the seawater, which would later be replaced by carbon dioxide from the atmosphere. The idea behind the iron-dust scheme is that the element is the pivotal ingredient that determines how much phytoplankton can grow on some regions of the ocean's surface. Phytoplankton are the microscopic plants on which most of the marine food chain is based. As phytoplankton grow, they pull carbon dioxide from the atmosphere and convert it into organic carbon, and it's this part of the process that interests environmental engineers. The tiny plants feed marine animals, and those creatures' fecal matter sinks and gets conveniently tucked away in the depths of the ocean. Where cold fusion would have heralded an era of plentiful, free energy, now carbon extracted from the atmosphere through iron fertilization holds the promise of solving the problem of climate change. However, Planktos's ploy to combat global warming by sequestering carbon in the oceans holds no water. The paper explains why.
Keywords: CO2.; Planktos; Algae bloom; Carbon dioxide; Carbon sequestration; Climate change; Cold fusion; Global warming; Iron dust; Iron fertilization; Marine food chain; Microscopic plants; Ocean surface; Organic carbon; Seawater; Surface phytoplankton